The effectiveness of virtual learning to enhance Higher-Order Thinking Skills in year 5 students - Mat, Hamidah; Mustakim, Siti Salina (Human Resource Management Academic Research Society, 2021)
In the 21st century, the education process should emphasize on learning to improve Higher-Order Thinking Skills (HOTS), providing rich and authentic experiences for inquiring, challenging, exploring, developing in-depth knowledge and understanding, and producing imaginative and innovative people. Based on preliminary studies performed over the past five years, information on the problems and needs of primary science education were gathered. The issue found is lack of teaching materials that facilitate the development of the higher-order thinking skills in students, which allow students to learn science independently hence improving their knowledge. This paper will look into the effectiveness of virtual learning to enhance HOTS among the students. Virtual learning, in many ways, have beneficial impacts on learners and communities. To improve the standard of learning according to teachers’ qualifications, it is currently essential to create an e-module virtual learning to improve primary school students' higher order thinking skills. This development is based on the view that e-modules are self-contained and self-instructed and can be used in independent learning.